High-speed video analysis of damped harmonic motion - J. Poonyawatpornkul (2018)
In this paper, we acquire and analyse high-speed videos of a spring-mass system oscillating in glycerin at different temperatures. Three cases of damped harmonic oscillation are investigated and analysed by using high-speed video at a rate of 120 frames s -1 and Tracker Video Analysis (Tracker) software. We present empirical data for the three cases of damped motion in graphical form. We also provide graphical proof of the relationship between the damped angular frequency and the damping constant. Finally, we determine the quality factors and give graphical proof of the dissipated energy of damped harmonic oscillators due to the viscosity of glycerin at different temperatures. These results will be developed into teaching material on the topic of damped harmonic motion. © 2013 IOP Publishing Ltd.